Factors Related to Diet Quality in Adolescent at Yadika 12 High School Depok - Zahra Fadhlina Hidayat; Avliya Quratul Marjan; Utami Wahyuningsih (Amerta Nutrition)
Background: Adolescents, a group with high nutritional needs, are facing the triple burden of malnutrition. Depok has the highest prevalence of overweight adolescents in Indonesia. Data shows an increase in the consumption of high-fat and high-sodium foods. Technological advancements have made foods more accessible, in 2020 Indonesia had the highest food delivery service usage in Southeast Asia. These factors may negatively impact adolescent diet quality, leading to health issues and higher risks of degenerative diseases.